Beneficiation and Technological Properties of Clays from Sabha South East of Libya - Alhadi M Ali Shiwa (Surman Journal of Science and Technology, 2025)
This research paper gives attention to the mineralogical and physical characterization of Sabha clays from Libya. Apart from that, the impending of the Sabha clays to the industrial application was also evaluated. The Sabha clays are geologically linked to Messak Formation of Jarmah Member and the industrial significance was not tested yet. Mineral recognition and characterization studies were accomplished using X-ray diffraction (XRD), differential thermal analyses (DTA), thermogravimetric analyses (TGA) and scanning electron microscopy with an energy dispersive X-ray spectrum (SEM-EDX) technique. Physical tests such as particle size, BET surface area, rheology, zeta potential, plasticity, colour, brightness, pH, cation exchange capacity and water content (W.C) was also performed. Based on the analyses, the Sabha clays are composed of kaolinite as its major phyllosilicate, whereas quartz occurs in minor amounts and could be used for industrial application.